Functional NIRS to detect covert consciousness in neurocritical patients. (December 2022) - Bicciato, Giulio; Narula, Gagan; Brandi, Giovanna; Eisele, Amanda; Schulthess, Sven; Friedl, Susanne; Willms, Jan Folkard; Westphal, Laura; Keller, Emanuela
Highlights: Cerebral response to music could be detected by fNIRS with an easy experimental protocol. Variation of low frequency oscillations is a possible biomarker of cortical responsiveness. fNIRS responsiveness was associated with consciousness and might predict the clinical outcome. Abstract: Objective: This pilot study assesses the feasibility to detect covert consciousness in clinically unresponsive patients by means of functional near infrared spectroscopy (fNIRS) in a real intensive care unit setting. We aimed to verify if the hemodynamic response to familiar music measured with fNIRS varies according to the level consciousness of the patients. Methods: 22 neurocritical patients and 6 healthy controls were included. The experiment consisted in 3 subsequent blocks including a first resting state recording, a period of music playback and a second resting state recording. fNIRS measurement were performed on each subject with two optodes on the forehead. Main oscillatory frequencies of oxyhemoglobin signal were analyzed. Spectral changes of low frequency oscillations (LFO) between subsequent experimental blocks were used as a marker of cortical response. Cortical response was compared to the level of consciousness of the patients and their functional outcome, through validated clinical scores. Results: Cortical hemodynamic response to music on the left prefrontal brain was associated with the level of consciousness of the patients and with their clinical outcome after three months. Conclusions: Variations in LFO spectral power measured with fNIRS may be a new marker of cortical responsiveness to detect covert consciousness in neurocritical patients. Left prefrontal cortex may play an important role in the perception of familiar music. Significance: We showed the feasibility of a simple fNIRS approach to detect cortical response in the real setting of an intensive care unit.